A Case Study of Investigation the impact of International Roughness Index in developing pavement deterioration model in the United Arab Emirates - ALSHEHYARI, KHAMIS ALI OBAID (2017)
Pavements characterized as an important infrastructure all over the world. As we all know UAE is becoming day to day famous over the worldwide therefore they are investing and focusing how to construct in a large network. Throughout the study, I have notified the core aim of this project is to find and demonstrate any correlation between some pavement condition parameters as can be IRI, rutting, deflection and cracking and to know if this hypothetical correlation can be used to determine and predict the behavior of some of them based in the knowledge of only one.